Slope Reliability Analysis in Locating and Observing the Direction of Failure Propagation - Djeffal, Houcine; Belkacemi, Smain (Engineering, Technology & Applied Science Research, 2023)
Slope stability analysis is traditionally carried out with the ultimate equilibrium methods. In these approaches, the global assessment of slope stability is obtained through the evaluation of the factor of safety. The strength parameters that allow the evaluation of resistant forces along the hypothetical slip surface are considered unique and constant. The shape of the stress-strain curve of the soil may substantially affect the stability of the soil mass over, particularly in the case of the potential of a progressive failure. As a part of this work, the influence of uncertainties on the peak and post-peak strength parameters and the impact of a progressive failure on the failure probability of a hypothetical slip surface are discussed. The conventional method of Morgenstern-Price of slope stability analysis consisted of locating the critical slip surface by evaluating the minimum factor of safety. The probability of failure was estimated using three different techniques, i.e. FORM, FOSM, and Monte Carlo simulation. This study improved the assessment of the impact of progressive failure on the risk of slope failure. The reliability analysis of slices allowed for locating the failure area and observing the direction of failure propagation.